First Salmon Covered in Down - G.F. MacDonald Collection (1972)
Re-enactment of the First Salmon Ceremony performed by the 'Ksan Performing Arts Group. The re-enactment is based on the narrative recorded by Franz Boas for the Gitselesu of Kitselas Canyon.